IDENTITAS BUDAYA SEKTOR AUDIOVISUAL DI IDENTITAS BUDAYA SEKTOR AUDIOVISUAL DI - Ana Windarsih (Jurnal Masyarakat dan Budaya, 2009)
Audiovisual sector is an important factor in American, because this sector gives growing revenue more than other sectors like automotive industry, transportation, manufacturing and petrochemicals. American has interest for growing industry that comfortable with imperialism system as an American’s ideology. In the other hand, for developing countries including Indonesian as importer products American have the amazing cultural identities. How struggle’s Indonesian defend cultural identities and what Indonesian’s cultural diversity can empower and can counter American products blooding. Key words: cultural identity, audiovisual sector, free trade